2018
DOI: 10.1177/0003489418783781
|View full text |Cite
|
Sign up to set email alerts
|

Priorities in the Neurotology Fellowship Match: A Survey Study of Program Directors and Fellows

Abstract: Among neurotology fellows, operative case load and breadth of surgical exposure are highly valued components of accredited fellowship training. Among neurotology fellowship program directors, candidates' performance during the fellowship interview appears to be highly valued, more so than the strength of applicants' letters of recommendation or prior research credentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…All of these studies found that surgical exposure, volume of surgery, caseload, and refinement of endoscopic surgery skills were considered highest priority when evaluating fellowship programs. 11 , 12 , 13 Applicant interest in program faculty is not unique to orthopaedic sports medicine fellowship applicants. Laryngology applicants considered a program’s emphasis on mentorship a component of highest importance when evaluating programs, and applicants to pediatric otolaryngology fellowships considered otology faculty reputation a component of greatest importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these studies found that surgical exposure, volume of surgery, caseload, and refinement of endoscopic surgery skills were considered highest priority when evaluating fellowship programs. 11 , 12 , 13 Applicant interest in program faculty is not unique to orthopaedic sports medicine fellowship applicants. Laryngology applicants considered a program’s emphasis on mentorship a component of highest importance when evaluating programs, and applicants to pediatric otolaryngology fellowships considered otology faculty reputation a component of greatest importance.…”
Section: Discussionmentioning
confidence: 99%
“…These components were identified after analyzing relevant literature for both orthopaedic subspecialty fellowship and other surgical subspecialties. 2 , 3 , 5 , 8 , 9 , 10 , 11 , 12 , 13 Survey participants were asked to rank each component on a 5-point Likert scale, ranging from “not at all important” to “very important.” The free response question at the end of the survey allowed participants to voluntarily share any other website information they considered important that was not included within one of the 3 categories.…”
Section: Methodsmentioning
confidence: 99%
“…Nearly all resources described specific areas of surgical exposure, but many programs did not provide an estimated operative volume. The aforementioned study evaluating neurotology fellowship web sites found that operative volume was the most important criterion considered by applicants 13 . This is likely to be of high interest to head and neck surgery fellowship applicants as well.…”
Section: Discussionmentioning
confidence: 98%
“…There is a growing body of literature concerned with the utility of information presented on fellowship and residency program web sites, both in otolaryngology 3,4 and in other specialties 5–11 . Moreover, several recent studies have identified factors important to fellowship applicants in a variety of otolaryngology subspecialties 12–14 . The present study aims to determine whether this information is readily available through the AHNS program directory and head and neck surgery fellowship web sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation